Biology is the new physics - Hunter, Philip (Nature Publishing Group, 2010)
The application of mathematics and computer science to biology is changing the nature of research. Philip Hunter explores the cross-fertilization of ideas between the disciplines and how it creates new job opportunities for biologists and mathematicians